The Application of Quantum Teaching to Improve Students' Learning Outcomes Online at SD Negeri 1 Mewek Purbalingga During The Pandemic - Setyaningrum, Dini (Universitas Sebelas Maret, 2020)
The purpose of this research was to improve student learning outcomes online through the application of the Quantum Teaching-Learning model at SD Negeri 1 Mewek, Kalimanah, Purbalingga. This type of research is called collaborative Classroom Action Research. The research took place in two cycles of action. Each cycle consisted of planning, implementing, observing, and reflecting activities. After the action research with the Quantum Teaching learning model in the first cycle, the average value of learning outcomes increased to 79, and students who achieved KKM were 76% of 17 students, while in the second cycle it increased to 82 and students who achieved KKM were 94% of 17 students. In addition, the application of Quantum Teaching in learning can also encourage students to be active physically, mentally, and socially.